The fiscal implications and social effects of the tax exemption policy in the Algerian economy - Fatma, Gaffaf; Drah, Karima Abdullah; Faiza, Dahmouche (The International tax journal, 2025)
The Tax Exemption Policy in Algeria significantly impacts both the fiscal landscape and social dynamics of the nation. This paper explores the policy's implications on government revenue, highlighting potential shortfalls and budgetary adjustments. Additionally, it examines the social consequences, including shifts in economic equity and access to essential services. By analyzing quantitative data and qualitative assessments, the study aims to provide a comprehensive understanding of how tax exemptions influence economic growth and social welfare in Algeria. This multifaceted approach underscores the necessity for balanced policy reforms that align fiscal responsibility with social equity.